Parents or Peers? Predictors of Prosocial Behavior and Aggression: A Longitudinal Study - Malonda, Elisabeth; Llorca, Anna; Mesurado, Belen; Samper, Paula; Mestre, M. Vicenta (Frontiers in Psychology, 2019)
The aim of this longitudinal study was to determine the associations among peer attachment, warmth from the mother and father, strict control by the mother and father, prosocial behavior, and physical and verbal aggression in adolescence. Few longitudinal studies have examined how peer attachment and parenting styles of the mother and father relate to prosocial behavior and aggression. Participants were 192 boys and 255 girls (M = 14.70 years; SD = 0.68) in wave 1. In the study participated 11 schools. For three successive years, participants reported on their fathers' and mothers' warmth and strict control, peer attachment, prosocial behavior, and aggression. Structural equations modelling was employed to explore two longitudinal models. Results show the influence of the mother and father on prosocial and aggression during adolescence. In addition, strong peer attachment predicted prosocial behavior in subsequent years. Therefore, the findings indicate that despite the increasingly important role of friends during the transition from childhood to adolescence, parenting styles play a key role in the personal and social development of their children. Programs aimed at preventing aggression should be designed considering the importance of stimulating and strengthening prosocial behavior, peer attachment and a family environment of affect, support and communication.